2002
DOI: 10.1093/annonc/mdf195
|View full text |Cite
|
Sign up to set email alerts
|

Neovastat (Æ-941) in refractory renal cell carcinoma patients: report of a phase II trial with two dose levels

Abstract: Neovastat is well tolerated by advanced cancer patients at doses of 60 and 240 ml/day. The higher dose of Neovastat administered in this trial is associated with a survival benefit in RCC, which is not explained by differences in major prognostic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(34 citation statements)
references
References 10 publications
1
31
0
1
Order By: Relevance
“…Furthermore, treatment of patients (n = 44) with recurrent and progressive glioblastoma multiforme with a combination of marimastat and an alkylating agent temozolomide resulted in increased progression-free survival at the time point of 6 months (34). In a small group of patients with advanced renal cell carcinoma, treatment with a higher dose of neovastat was associated with longer survival than treatment with a lower dose (35).…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, treatment of patients (n = 44) with recurrent and progressive glioblastoma multiforme with a combination of marimastat and an alkylating agent temozolomide resulted in increased progression-free survival at the time point of 6 months (34). In a small group of patients with advanced renal cell carcinoma, treatment with a higher dose of neovastat was associated with longer survival than treatment with a lower dose (35).…”
Section: Discussionmentioning
confidence: 91%
“…A phase I/II trial of shark cartilage found no clinical benefit [52]. Neovastat, another cartilage extract, was associated with a survival benefit in renal cell carcinoma in higher versus lower doses [53]. However, that trial was not randomized.…”
Section: Biologic Treatmentsmentioning
confidence: 99%
“…A phase-I trial of AE-941 was performed in 144 patients with refractory solid tumors, including patients with metastatic RCC. As shown on Table II, treatment with AE-941 (either an escalated or high single dose), resulted in an objective response in a mere 14% of patients [Batist et al, 2002].…”
Section: Targeting Angiogenesis In Rcc: Therapeutic Outcomes and Clinmentioning
confidence: 97%
“…AE-941 (Neovastat) is a pure shark cartilage compound that selectively inhibits −2, −9, and −12 and competes for the binding of VEGF to its receptor (VEGFR-2), resulting in endothelial cell apoptosis [Batist et al, 2002]. A phase-I trial of AE-941 was performed in 144 patients with refractory solid tumors, including patients with metastatic RCC.…”
Section: Targeting Angiogenesis In Rcc: Therapeutic Outcomes and Clinmentioning
confidence: 99%